К дискуссии о языке хазар - Петрухин, В.Я. (Хазарский альманах, 2016)
Несмотря на некоторые спорные моменты, автор статьи в целом поддерживает концепцию О. А. Мудрака о наличии некоторых имен кавказского происхождения в средневековых хазарско-еврейских письменных источниках. In spite of some controversial moments the author of this article supports generally the O. A. Mudrak’s conception on the presence of some names of Caucasian origin in the medieval Khazar-Jewish written sources.